AUDIOBOOK ISLAMI UNTUK PENYANDANG DISABILITAS SLB KATEGORI A - Maya Rini Handayani (At-Taqaddum, 2016)
The Indonesian government has launched a 9-year compulsory education program for all students in Indonesia. The word "all" should have been touching all levels of society including the blind students. However, the fact shows different condition. Many schools still refuse to accept the blind students. In addition, some facilities like braille books for the blind students are also still limited while these books become the main pillar of education. They still become such "luxury stuffs" for the blind students in Indonesia.The cost of producing Braille books equals with fourfold financing regular books. This is because the Braille books need heavier papers, approximately 120 grams for every sheet of paper. To resolve this problem is by creating an audiobook or better known as a "voiced book" for the blind students. The extraordinary school (SLB) of category A is an outstanding school specifying for the blind students in Semarang who desperately need an audiobook.This audiobook has many benefits for the blind students of SLB category A. Firstly, it facilitates the students to "read" a book through the hearing sense. Secondly, it minimizes the cost of school expenditures in the book procurement both regular books for teachers or braille books for students. At last, it supports the government program of campaigning ”paperless office”.